2012
DOI: 10.1242/jeb.068940
|View full text |Cite
|
Sign up to set email alerts
|

Directional cues inDrosophila melanogasteraudition: structure of acoustic flow and inter-antennal velocity differences

Abstract: SUMMARYDrosophila melanogaster have bilateral antisymmetric antennae that receive the particle velocity component of an acoustic stimulus. Acoustic communication is important in their courtship, which takes place in the acoustic near-field. Here, the small size of the dipole sound source (the male wing) and the rapid attenuation rate of particle velocity produce a spatially divergent sound field with highly variable magnitude. Also, male and female D. melanogaster are not usually stationary during courtship, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 38 publications
3
63
1
Order By: Relevance
“…This arises in part from the small size of their wings—each wing maximally generates only ~10 −16 W of power, which is roughly six orders of magnitude below the threshold of human hearing (Bennet-Clark, 1971). In addition, the Drosophila ear (its arista) is most sensitive to the particle velocity component of sound, which is heavily attenuated with increasing distance from a point source (Göpfert and Robert, 2002; Morley et al, 2012). To increase the probability that the female hears his song, the male could continually sing at maximal intensity, but this runs the risk of saturating her auditory system and consequently making his communication signal less effective.…”
Section: Discussionmentioning
confidence: 99%
“…This arises in part from the small size of their wings—each wing maximally generates only ~10 −16 W of power, which is roughly six orders of magnitude below the threshold of human hearing (Bennet-Clark, 1971). In addition, the Drosophila ear (its arista) is most sensitive to the particle velocity component of sound, which is heavily attenuated with increasing distance from a point source (Göpfert and Robert, 2002; Morley et al, 2012). To increase the probability that the female hears his song, the male could continually sing at maximal intensity, but this runs the risk of saturating her auditory system and consequently making his communication signal less effective.…”
Section: Discussionmentioning
confidence: 99%
“…Phase cues can reduce this ambiguity. For example, sound coming from the left or right will cause the antennae to move out of phase, whereas sound coming from the front or back will cause the antennae to move in phase (Morley et al, 2012). The brain could use phase information to reduce ambiguity even further – for example, to determine whether the sound source is in front or in back – because Drosophila courtship song pulses have a stereotyped phase profile (Arthur et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, Morley et al . () demonstrated that the mechanical sensitivity of the arista changes as a function of the angle of incidence of the acoustic stimulus. Suggestively, males of D. buzzatii produce secondary songs later in courtship and immediately before copulation (Oliveira et al ., ; Iglesias & Hasson, ).…”
Section: Discussionmentioning
confidence: 99%